NF-E2-Related Factor 2 and Its Role in Diabetic Nephropathy (Iranian Journal of Kidney Diseases, 2013)
Diabetic nephropathy is the leading cause of chronic kidney disease and end-stage renal disease. Oxidative stress has been recognized as a major contributor to its pathogenesis. Defensive mechanisms have also widely been studied. One of them, the NF-E2-Related Factor 2, is reviewed in this article.